Implementasi Pendekatan Culturally Responsive Teaching (CRT) Pada Pembelajaran Fisika Untuk Meningkatkan Motivasi Belajar Peserta Didik: Anggi Larasati, Titin Sunarti, Budiwati - Larasati, Anggi; Sunarti, Titin; B, Budiwati (Universitas Negeri Surabaya, 2023)
This research is motivated by the low motivation of students to learn physics at SMA Negeri 1 Wonoayu. Based on the preliminary study conducted by the author in Class XI-3, it shows that 51.2% of students have low motivation to learn physics. Learning that is solely based on textbooks and not connected to the students' conditions, including their past experiences and their social and cultural backgrounds, can lead to low student participation and motivation. Therefore, efforts are needed from teachers to make physics learning more engaging, one of which is by implementing the Culturally Responsive Teaching (CRT) approach. CRT is a teaching approach that utilizes students' cultural references as a means to learn a subject matter. This research is a collaborative classroom action research conducted in two cycles. Data related to student motivation was obtained through a motivation questionnaire, while student learning outcomes in the knowledge domain were obtained through written tests. The research results show a significant improvement in physics learning motivation, starting from the initial observation, Cycle 1, and ending in Cycle 2, which are 48.8%, 70.5%, and 82.9%, respectively. Additionally, student learning outcomes also improved from Cycle 1 to Cycle 2, increasing from 61.1% to 94.4%. This indicates that the implementation of the CRT approach in physics learning is effective in enhancing student motivation and learning outcomes.